PERILAKU PENGUSAHA E-COMMERCE TERHADAP KEPATUHAN PEMBAYARAN PAJAK PENGHASILAN (PPH 25) - Nusa, Yahya (Restitusi : Jurnal Riset Perpajakan, 2022)
The purpose of this study is to determine and analyze the effect of the behavior of S-commerce entrepreneurs on income tax payment compliance and how much influence the behavior of S-commerce entrepreneurs on income tax payment compliance. Type of research in this study uses a quantitative survey research type. The sample in the study was 20 people as respondents. The results showed that the results of the statistical calculation of the t-test. In the behavior of E-commerce entrepreneurs, the value of t = 11,187 with p (Sig.) = 0.000. This shows that the p value <0.05 so that H0 is rejected, it can be concluded that there is a significant effect of the behavior of s-commerce entrepreneurs (X) on the variable of income tax payment compliance (Y) and the large influence of the behavior of s-commerce entrepreneurs on compliance. income tax payment of 87.4%.